Integration of the social determinants of health into quality indicators for colorectal cancer surgery: a scoping review protocol - Natalie G Coburn; Julie Hallet; Rinku Sutradhar; Harsukh Benipal; Aisha Lofters; Tiago Ribeiro; Adom Bondzi-Simpson; Victoria Barabash; Rebecca A Snyder; Callisia Clarke (BMJ Open, 2023)
Introduction Quality monitoring is a critical component of high-performing cancer care systems. Quality indicators (QIs) are standardised, evidence-based measures of healthcare quality that allow healthcare systems to track performance, identify gaps in healthcare delivery and inform areas of priority for strategic planning. Social structures and economic systems that allow for unequal access to power and resources that shape health and health inequities can be described through the social determinants of health (SDoH) framework. Therefore, granular analysis of healthcare quality through SDoH frameworks is required to identify patient subgroups who may experience health inequity. Given the high burden of disease of colorectal cancer (CRC) and well-defined cancer care pathways, CRC is often the first disease site targeted by health systems for quality improvement. The objective of this review is to examine how SDoH have been integrated into QIs for CRC surgery. This review aims to address three primary questions: (1) Have SDoH been integrated into the development, reporting and assessment of CRC surgery QIs? (2) When integrated, what measures and statistical methods have been applied? (3) In which direction do individual SDoH influence QIs outputs?Methods This review will follow Arksey and O’Malley frameworks for scoping reviews. We will search MEDLINE, EMBASE, HealthSTAR databases for papers that examine QIs for CRC surgery applicable to healthcare systems from database inception until January 2023. Interventional trials, prospective and retrospective observational studies, reviews, case series and qualitative study designs will be included. Two authors will independently review all titles, abstracts and full texts to determine which studies meet the inclusion criteria.Ethics & dissemination No ethics approval is required for this review. Results will be disseminated through scientific presentation and relevant conferences targeted for researchers examining healthcare quality and equity in cancer care.Registration details osf.io/vfzd3-Open Science Framework.